Persepsi Guru tentang Kompetensi Kepribadian Tenaga Administrasi Sekolah di SMAN Se Kota Pariaman - Novianti, Tesa; Rifma, Rifma (Lembaga Yasin AlSys, 2024)
School administration personnel have a strategic role in providing administrative services to support the learning process at school. This study aims to describe teachers' perceptions of the personality competence of school administration personnel in public high schools in Pariaman City which includes aspects of integrity and noble character, work ethic, self-control, self-confidence, flexibility, thoroughness, discipline, creativity and innovation, and responsibility. This research uses quantitative descriptive method with simple random sampling technique. Data were collected using a questionnaire distributed to teachers of public high schools in Pariaman City. The results showed that overall teacher perceptions of the personality competence of school administration personnel were in the “Good” category with an average score of 4.44. Aspects of integrity and noble character obtained the “Very Good” category (4.69), while other aspects were in the “Good” category with a score range of 4.33-4.45. The implications of this study indicate the need to maintain and improve the personality competence of school administration personnel, especially in the aspect of self-control which obtained the lowest score, to optimize school administration services.